Peace Education and Spirituality at the United Nations: Tai Ji Men and the Road to the International Day of Conscience - Šorytė, Rosita (The journal of CESNUR, 2023)
Days of observance included in the United Nations official calendar may be proposed by NGOs but need the support of member states to be approved. The article explores Tai Ji Men's narrative about education, peace, and conscience, how the movement was able to gather international support for its discourse, and how some states, including Bahrain, saw a political advantage in embracing and endorsing the proposal of the International Day of Conscience. It further describes the road to the 2019 UN resolution on the International Day of Conscience and tries to answer the question how a comparatively little-known Asian spiritual movement was able to persuade most of the United Nations member states that the link between education, peace, and conscience should be symbolically reaffirmed at the global level, and to endorse a proposal that was in fact rooted in a specific spiritual worldview.